Status and challenges of ISO 9001 quality system adoption among wooden furniture manufacturers in Malaysia and Vietnam - Ratnasingam, Jegatheswaran; Ioras, Florin (Maney Publishing, 2014)
The ISO 9001 quality system is being advocated as a management tool to boost the performance of wooden furniture manufacturers in the South East Asian region. A study was therefore conducted to evaluate the status and challenges of the ISO 9001 quality system adoption among wooden furniture manufacturers in Malaysia and Vietnam. The data were compiled through direct-interviews of 100 wooden furniture manufacturers (of which 25 were ISO 9001 certified companies) using a structured questionnaire, which had four parts. The results found that ISO 9001 adoption was relatively low among furniture manufacturers due to its high implementation cost and lack of market demand, although the ISO 9001 certified companies were much more productive than their non-certified counterparts. It was also apparent that the certified furniture manufacturers were focused on producing quality furniture cost effectively, derived primarily from their lower degree of operational inefficiencies. Nevertheless, the demand for ISO certification is market-specific, as Japanese, Korean, European and Middle Eastern furniture buyers show preferences for dealing with certified companies. Therefore, the benefits of ISO 9001 quality system through greater market access and increased productivity in the mills must become more apparent, before significant adoption among wooden furniture manufacturers can be realised.